Glycemic and insulinemic responses to commercially available beverages, consumed during recovery from swim training - Payne, W.; Thomson, C. D.; Rose-Peddie, M. C.; Perry, T. L. (Medicina Sportiva, 2012)
To investigate the impact of consuming commercially available beverages on glycemic and insulinemic response during recovery from exercise. Methods: Seven female and seven male adolescent competitive swimmers completed three trials in a randomized order. Commercially available beverages were consumed in volumes providing 1.2 g CHO·kg-1 body mass upon completion of a standardized swim training session, with a second feeding of the same beverage provided 60 min later. Blood samples were taken prior to, and 15, 30, 45, 60, 90 and 120 min after consumption of the first serving of the beverage for analysis of insulin and glucose. Results: The carbohydrate sport beverage produced a significantly larger (P < 0.001) glucose incremental area under the curve than the sports specific meal replacement beverage and the meal replacement beverage. There were no differences between beverages in insulin incremental area under the curve. Consumption of the carbohydrate sports beverage resulted in higher ratings of gut fullness and lower ratings of hunger 30 min after consumption, compared to a sports specific meal replacement beverage and a standard meal replacement beverage. These differences were not evident 60 min after consumption of the beverages. Conclusions: Commercially available beverages are convenient, and are frequently used by athletes during post-exercise recovery. The carbohydrate sports beverage elicited a larger glucose response compared to the other beverages used in this study. This higher glycemic response is favorable, especially when the time before the next training bout or competition is short and a quick and optimal recovery is paramount.